KAJIAN LITERATUR TENTANG MEDIA BANGUN RUANG SEBAGAI PENGUAT PEMAHAMAN KONSEP VOLUME DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Dhita Yuli Ariyani; Hinda Nur Khairiyah; Opi Amelia; Azamul Fadhly Noor Muhammad (STKIP Subang, 2025)
Mathematics learning in elementary schools requires instructional media that are appropriate to students’ cognitive development, as learners are still in the concrete operational stage. One mathematical topic that is often difficult for students to understand is the concept of volume of three-dimensional shapes. This article aims to systematically review previous studies on the use of three-dimensional geometry media as a means of strengthening students’ understanding of volume concepts in elementary school mathematics learning. The method used in this study was a literature review by analyzing ten relevant national journal articles obtained through Google Scholar using the keywords three-dimensional geometry media, volume concepts, mathematics learning, and elementary school. The analyzed data included research subjects, types of media used, research methods, and research findings. The results of the review indicate that three-dimensional geometry media, including concrete models, interactive media, instructional videos, Android-based media, and augmented reality, are effective in improving students’ conceptual understanding of volume, learning outcomes, learning activities, and learning motivation. These media help students visualize abstract concepts concretely and connect mathematical ideas with real learning experiences. Therefore, the use of three-dimensional geometry media is recommended as an effective instructional strategy to enhance students’ understanding of volume concepts in elementary school mathematics learning. Keywords: Three-Dimensional Geometry Media, Volume Concept, Mathematics Learning